2017
DOI: 10.1017/s1744133117000123
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory theory: commercially sustainable markets rely upon satisfying the public interest in obtaining credible goods

Abstract: Regulatory theory is premised on the failure of markets, prompting a focus on regulators and industry from economic perspectives. This article argues that overlooking the public interest in the sustainability of commercial markets risks markets failing completely. This point is exemplified through health care markets - meeting an essential need - and focuses upon innovative medicines as the most desired products in that market. If this seemingly invulnerable market risks failure, there is a pressing need to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…On average, five to six articles were published each year and of 65 articles, 38 (58%) were published from 2010 to 2015 and 27 (42%) were published from 2016 to 2020. Several articles referred to the US Food and Drug Administration's (FDA) definition of innovation in the USA [21][22][23][24][25][26][27][28][29], the National Institute for Health and Care Excellence's (NICE) including Kennedy's short study for NICE in the UK [30][31][32][33][34][35][36][37] and the Amelioration du service [38][39][40][41][42]. The most common factor considered while defining innovation was therapeutic benefit as a measure of innovativeness across countries.…”
Section: Definitions Of Innovationmentioning
confidence: 99%
See 3 more Smart Citations
“…On average, five to six articles were published each year and of 65 articles, 38 (58%) were published from 2010 to 2015 and 27 (42%) were published from 2016 to 2020. Several articles referred to the US Food and Drug Administration's (FDA) definition of innovation in the USA [21][22][23][24][25][26][27][28][29], the National Institute for Health and Care Excellence's (NICE) including Kennedy's short study for NICE in the UK [30][31][32][33][34][35][36][37] and the Amelioration du service [38][39][40][41][42]. The most common factor considered while defining innovation was therapeutic benefit as a measure of innovativeness across countries.…”
Section: Definitions Of Innovationmentioning
confidence: 99%
“…UK In the UK, "innovation in the area where there is an unmet need that improves outcomes and ensures value for money to the National Health Service (NHS) with better access to effective medicines" is defined as innovation [46]. According to NICE, innovation is defined as a treatment that produces demonstrable and distinctive benefits of a substantial nature that may not be adequately captured in the quality-of-life measure used [31,32]. Kennedy in his short study for NICE [30,33,34], suggested that innovation is something that is new, improves on existing interventions, and offers something more in the way of a step change in terms of outcomes for patients.…”
Section: Definitions Of Innovationmentioning
confidence: 99%
See 2 more Smart Citations